Designing Logical Sequence by Using Microcontroller as Security Tools - Aminudin, Nur; Feriyanto, Dwi; Salimu, Salman Alfarisi; Wicaksono, Garda Arif; Cahyadi, Septian; Sukamto, Anton; Rahman, Taufik (Program Studi Teknik Elektro Universitas Khairun, 2024)
The objective of this paper are 1) to tell how to design logical security tools by using microcontroller 2) to describe the sequence of designing logical using microcontroller toward security controller. To explain the sequence step by step the researcher used design electronic chain. An Embedded system usually consists of at least a system unit microprocessor its memory for the program, data also input or output interface simple system. The interface like floppy disk, keyboard, appearance or printer which are usually available on the personal computer exactly is not available at the micro control system.Â Microcontroller systems are used for important simple works like control motors, switch, variable resistor or electronic device, one of micro control used is box control or safe deposit boxes such as house, office, or bank for safe security. By utilizing micro control, the owner has valuables are not felt worried about the safe deposit box from stolen